Study of Public Elementary School Regrouping in Magelang to Improve Education Quality Management - Sri Haryati; Sukarno Sukarno; Astuty Astuty; Ahmad Muhlisin; Suwito Singgih (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
The research describes an analysis of regrouping public elementary school implementation plans in Magelang. The research method used is a qualitative method with instruments of open interview sheets and documents. The research results indicate that schools eligible for the regrouping consist of 1) SDN Wates 1 with SDN Wates 5; 2) SDN Rejowinangun Utara 2 with SDN Rejowinangun Utara 3; 3) SDN Kramat 2 with SDN Kramat 3. At the same time, schools that are less eligible for the regrouping include SDN Magersari 1 and SDN Magersari 3 since each school has unique characteristics that require special handling. Recommendations or suggestions that the regional department of education can apply are 1) intensive coordination or communication with all stakeholders; 2) unique approaches to potential resistant parties; 3) the design of the utilization of regrouped school assets; and 4) post-regroup buildings to meet the mandatory affairs of the Regional Government in the Education sector, such as community activity center (SKB) building, the secretariat of school supervisors, education council, and integrated art Council. The research implication becomes a reference in improving education quality in Magelang city through elementary school regrouping.